2023
DOI: 10.3390/mi14030673
|View full text |Cite
|
Sign up to set email alerts
|

PDMS Micropatterns Coated with PDA and RGD Induce a Regulatory Macrophage-like Phenotype

Abstract: Regulatory macrophages (Mreg) are a special cell type that present a potential therapeutic strategy for various inflammatory diseases. In vitro, Mreg generation mainly takes 7–10 days of treatment with chemicals, including cytokines. In the present study, we established a new approach for Mreg generation using a three-dimensional (3D) micropatterned polydimethylsiloxane (PDMS) surface coated with a natural biopolymer adhesive polydopamine (PDA) and the common cell adhesion peptide motif arginylglycylaspartic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
2
4
0
Order By: Relevance
“…We did not use M-CSF and IFN-γ, which are commonly used to generate human Mregs [ 11 ]. Our Mregs had an elongated morphology, which was in line with other findings [ 15 , 40 ], and were phenotypically characterized as CD11b hi , CD14 lo , CD16 + , CD33 + , CD80 lo , CD86 + , iNOS - , CD163 hi , CD206 + , CD209 + , CD274 +/hi , TREM-2 + , MER-TK hi , and DHRS9 +/hi . Most of the markers evaluated herein were expressed in the Mregs generated by others, including CD14, CD80, CD86 [ 15 , 21 , 41 ], CD163, CD206, CD274 [ 15 , 42 ], CD209, MER-TK [ 15 ], and DHRS9 [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not use M-CSF and IFN-γ, which are commonly used to generate human Mregs [ 11 ]. Our Mregs had an elongated morphology, which was in line with other findings [ 15 , 40 ], and were phenotypically characterized as CD11b hi , CD14 lo , CD16 + , CD33 + , CD80 lo , CD86 + , iNOS - , CD163 hi , CD206 + , CD209 + , CD274 +/hi , TREM-2 + , MER-TK hi , and DHRS9 +/hi . Most of the markers evaluated herein were expressed in the Mregs generated by others, including CD14, CD80, CD86 [ 15 , 21 , 41 ], CD163, CD206, CD274 [ 15 , 42 ], CD209, MER-TK [ 15 ], and DHRS9 [ 22 ].…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, in an M2-favorable environment, the RGD motif facilitated the M2 polarization of the macrophages [ 53 , 54 ]. In our recent study, we demonstrated that THP-1 cells cultured on RGD- and polydopamine-coated micropatterns were able to induce their differentiation into Mregs-like cells, even in the absence of cytokines [ 40 ]. Additionally, integrin (which is a counterpart to RGD) was also involved in M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…It can improve cell attachment from cell-incompatible surfaces. The PDA-coated surfaces have shown enhanced cell compatibility and viability as described in our previous studies [14][15][16]. Similarly, PDA surface modification of PCL nanofiber can reduce their low cell adhesion [17][18][19].…”
Section: Introductionsupporting
confidence: 62%
“…This regulatory phenotype was characterized by elongated fiber-like morphology and high expression of CD163/206/209/274, MER-TK, TREM2 and DHRS9. 63 Chen and colleagues investigated the effects of biomimetic calcium phosphate (BioCaP) coating, with or without bone morphogenetic protein 2 (BMP2), on the polarization of pre-stimulated M1 macrophages. 64 The mRNA expression of TNF-α was upregulated in M1 macrophages co-cultured with BioCaP and BioCaP + Inc.BMP2 coatings on day 1, followed by its downregulation on days 3 and 5.…”
Section: Effects Of Biomaterials Properties On the Immune Response Of...mentioning
confidence: 99%